Faktor-Faktor Yang Berhubungan Dengan Status Fungsional Dan Kesehatan Mental Post Covid-19 - Edian Fitriana; Dewi Gayatri; Muhammad Adam; Tuti Herawati (Journal of Health Science and Prevention, 2022)
The new coronavirus disease 2019 (Covid-19) has been declared a pandemic by WHO. The transmission of Covid-19 is robust and the infection rate is fast. This systematic review aims to analyze and review the currently published literature related to factors associated with functional status and mental health in post-Covid-19 patients. The method used is by searched the relevant databases and assessed research articles that met the inclusion and exclusion criteria. After an initial screening of articles identified by the title and abstract, 167 were selected. Furthermore, 52 full-text articles were assessed and reviewed against our inclusion criteria and thus 16 articles were deemed eligible and analyzed in this analysis. All studies included an adult population between 18 and 95 years. The median length of hospitalization for Covid-19 patients ranged from 12 days to 21 days.  The most common long-term symptoms in Covid-19 patients include: shortness of breath, fatigue, decreased physical function, insomnia, impaired cognitive function, depression, and anxiety. Factors that influence it besides demographics also include the length of hospitalization, The severity of illness, and the presence of comorbidities. Therefore, having the right support and treatment with the proper management strategy can help restore and improve their health after being discharged from the hospital